2013
DOI: 10.1016/j.snb.2012.09.109
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of AlInN barrier ISFET structures with GaN capping for pH detection

Abstract: The pH response of GaN/AlInN/AlN/GaN ion-sensitive field effect transistor (ISFET) on Si substrates has been characterized. We analyzed the variation of the surface potential (AV sp /ApH) and current (A/ ds /ApH) with solution pH in devices with the same indium content (17%, in-plane lattice-matched to GaN) and different AlInN thickness (6 nm and 10 nm), and compared with the literature. The shrinkage of the barrier, that has the effect to increase the transconductance of the device, makes the 2-dimensional el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…It could be observed that the influences of interfering N + and K + ions on the studied ISFET are negligible. Comparisons of pH sensing performance among Device A and previously reported works are listed in Table 2 [20][21][22][23][24][25][26]. Although the highest average sensitivity (54.88 mV/pH) of treated ISFET is not outstanding as compared to previous works, the pH sensing performance is remarkably enhanced (∼26% improvement) by a simple H 2 O 2 surface treatment.…”
Section: Resultsmentioning
confidence: 92%
“…It could be observed that the influences of interfering N + and K + ions on the studied ISFET are negligible. Comparisons of pH sensing performance among Device A and previously reported works are listed in Table 2 [20][21][22][23][24][25][26]. Although the highest average sensitivity (54.88 mV/pH) of treated ISFET is not outstanding as compared to previous works, the pH sensing performance is remarkably enhanced (∼26% improvement) by a simple H 2 O 2 surface treatment.…”
Section: Resultsmentioning
confidence: 92%
“…The enhanced hydrogen and hydroxyl ions adsorption capability improves the variation of the surface potential. The relationship between ( I DS / pH) and ( ψ s / pH) is realized as [12]:…”
Section: Resultsmentioning
confidence: 99%
“…Sensing membrane plays an important role for the ISFET since the site-binding model reveals that the sensitivity of the ISFET is determined by the amount of hydroxyl adsorption on the sensing membrane which causes the surface potential variation in different pH buffer solution. Some research have used the AlGaN [11] and GaN cap layer [12] as the sensing membrane. Although the aforementioned fabrication processes of the ISFET are much easier, surface defects affect performances of AlGaN/GaN ISFET dramatically.…”
mentioning
confidence: 99%
“…The realisation of reference electrode free measurements permits the fabrication of small, robust and on-chip AlGaN/GaN FET-based sensors, providing a clear advantage over existing glass electrode based pH and ion sensors. Although referenceelectrode free pH sensing has been demonstrated [12], [13], the scope of the reported investigations has been limited in terms of reference electrode free sensor optimization. Ion sensitivity in reference electrode free sensors has been shown to depend on AlGaN/GaN composition [14], which is not surprising given that the heterostructure design determines sheet carrier density.…”
Section: Introductionmentioning
confidence: 99%
“…Referenceelectrode free devices require a different approach, and device sensitivity in terms of induced surface potential needs to be extracted from I DS or V DS often employing simplifying approximations [16], [17]. In terms of heterostructure design, Brazzini et al recently demonstrated AlInN/ GaN-based sensors with high sensitivity even when employed in reference electrode free measurement configuration [13].…”
Section: Introductionmentioning
confidence: 99%